Трест в металлургической промышленности Российской империи в 1908 г.: позиция общества и правительства - Забудкова, О.А. (Культура народов Причерноморья, 2013)
В статье рассматривается влияние на общественное мнение и взгляды правительства
П.А. Столыпина проекта создания треста металлургических заводов Донбасса и Приднепровья.
Установлено, что попытка его создания стала переломным моментом в отношении к промышленным
монополиям со стороны общественности и органов власти. Отмечена крайне негативная позиция
широких слоев населения относительно монополий. Указывается на факт перехода правительства от
поощрения создания монополистических объединений к политике лавирования с сохранением контроля
над экономикой страны. У статті розглядається вплив на суспільну думку та погляди уряду П.А. Столипіна проекту
створення тресту металургійних заводів Донбасу та Придніпров’я. Встановлено, що спроба його
створення стала переломним моментом у ставленні до промислових монополій з боку громадськості та
органів влади. Відзначено вкрай негативну позицію широких верств населення стосовно монополій в
цілому. Зазначається перехід уряду від заохочення створення монополістичних об’єднань до політики
лавірування із збереженням контролю над економікою країни. The article examines the impact on public opinion and the views of Peter Stolypin government in
terms of project of creating the trust of metallurgical plants in Donbas and Dnieper region in 1908. It is
established that the attempt of its creation was a turning point as to an attitude of the society and the Russian
Empire authorities to industrial monopolies. The general public had an extremely negative attitude concerning
monopolies. It was relevant to fusion of metallurgical plants. Zemstvos and the State Duma position on this issue
was considered separately. The author draws attention to the uncertainty of the position of the Minister of
Finance Vladimir Kokovtsov and the Minister of Trade and Industry Ivan Shipov on the issue of monopoly
capital in the industry. The article discusses the fact of government transition from stimulating the establishment
of monopolies to a policy of maneuvering with keeping control over the economy of the country.
The conclusion is that an attempt to create a trust in the steel industry was the impetus to recognition by the
government the need of legislative regulation of monopolies, and intensified anti-monopoly public performances
of the Russian Empire.